Utility of Stereolithographic Models in Osteocutaneous Free Flap Reconstruction of the Head and Neck. Issue 2 (June 2013) - Morris, L.; Sokoya, Mofiyinfolu; Cunningham, Larry; Gal, Thomas J.
Background: Stereolithographic (SLA) models have become a valuable resource in preoperative planning in maxillofacial reconstruction. The objective of this study was to perform a defect specific analysis of the utility of SLA models. The goal was to determine the manner in which the perceived benefit of preoperative modeling translates to measurable clinical advantages. Methods: Patients who underwent reconstruction of defects of the mandible or midface using SLA modeling between 2006 and 2011 were identified through billing records. Based on the nature and extent of bony defect, cases requiring nearly identical reconstruction, but without modeling, were matched case by case for comparison. Given the presumed efficiency of SLA modeling, a comparison of total and reconstructive operative times was performed to see if this could offset the cost of the model. Results: There were 10 patients each in the "model" and "nonmodel" group. No significant differences were observed for total operative time between groups. Surprisingly, the total reconstructive time was lower in the group not using SLA models ( p = 0.05). Conclusions: SLA models provide several operative planning advantages, but did not appear to decrease operative time enough to sufficiently offset the cost of the model in this group.